1988
DOI: 10.1128/jvi.62.12.4510-4522.1988
|View full text |Cite
|
Sign up to set email alerts
|

The herpes simplex virus type 1 alpha protein ICP27 can act as a trans-repressor or a trans-activator in combination with ICP4 and ICP0

Abstract: The herpes simplex virus type 1 (HSV-1) a proteins ICP4, ICPO, and ICP27 are transacting proteins which affect HSV-1 gene expression. To investigate potential interactions between these a products and to determine the specificity of action of the a proteins in combination with each other compared with their activities individually, we performed a series of transient-expression assays. In these assays we used plasmids containing the a genes encoding ICP4, ICPO, and ICP27 either singly or in combination as effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
147
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(155 citation statements)
references
References 97 publications
8
147
0
Order By: Relevance
“…The CAT activity was normalized to the /3-galactosidase activity to correct for differences in transfection efficiency among different DNA precipitates. To compare the promoter activity across the different cell lines, the CAT activity driven by each reporter construct was compared with that driven by equimolar pRS V-CAT or pICP4-CAT plasmids, which contain the Rous sarcoma virus (RSV) enhancer/promoter and the herpes simplex virus ICP4 gene enhancer/promoter, respectively (Sekulovich et al, 1988) (generously given by Dr. R. M. Sandri-Goldin at University of California, Irvine). Our preliminary experiments showed that pRSV-CAT and pICP4-CAT, but not pSV4O-CAT, exert comparably high levels of promoter activity in neuronal and nonneuronal cell lines used in this study.…”
Section: Cell Culture Transfection and Enzyme Assaysmentioning
confidence: 99%
“…The CAT activity was normalized to the /3-galactosidase activity to correct for differences in transfection efficiency among different DNA precipitates. To compare the promoter activity across the different cell lines, the CAT activity driven by each reporter construct was compared with that driven by equimolar pRS V-CAT or pICP4-CAT plasmids, which contain the Rous sarcoma virus (RSV) enhancer/promoter and the herpes simplex virus ICP4 gene enhancer/promoter, respectively (Sekulovich et al, 1988) (generously given by Dr. R. M. Sandri-Goldin at University of California, Irvine). Our preliminary experiments showed that pRSV-CAT and pICP4-CAT, but not pSV4O-CAT, exert comparably high levels of promoter activity in neuronal and nonneuronal cell lines used in this study.…”
Section: Cell Culture Transfection and Enzyme Assaysmentioning
confidence: 99%
“…The 63-kDa IE protein (IE63 or ICP27) encoded by the UL54 gene (26) is a nuclear phosphoprotein and is one of two IE proteins essential for lytic virus replication. IE63 plays a key role in the switch from early to late gene expression (37,39), and this multifunctional protein has both trans-repressor and trans-activator functions (11,30,43,44). Transfection studies have demonstrated that IE63 acts synergistically with IE pro-teins IE175 and IE110 to repress expression from IE and early promoters and activate expression from late promoters (11,30,43); IE63 also affects the cellular localization of these two IE proteins (41,44).…”
mentioning
confidence: 99%
“…Transcription of these genes can occur in HSV-infected cells in the absence of protein synthesis, and at least four of these gene products, ICP4, -0, -22, and -27, are regulators of subsequent HSV gene expression (11,15,28,36,(40)(41)(42)(43)57). Furthermore, ICP4 and ICP27 can negatively regulate ␣ genes (11,15,36,39,(41)(42)(43)49). The ␤ genes are expressed prior to the onset of HSV DNA replication but require ␣-gene expression.…”
mentioning
confidence: 99%